Psychological Barriers and Resources of the Future Primary School Teachers’ Professional Success: The Cognitive Aspect - Handzilevska, Halyna; Plyska, Yuriy; Shershnova, Olena; Shturkhetskyy, Serhiy; Shyriaieva, Tetiana (Journal of Education Culture and Society, 2023)
Aim. The article represents the results of research into the success of the students who are preparing themselves for teaching activity in the nearest future while obtaining their professional education. The aim of this research is to examine the notion of professional success, with the focus on the cognitive component of this process through the prism of purpose in life. Methods. In accordance with a developed theoretical model of the professional success achieved by a person, empirical research was carried out on a sample of the future primary school teachers with the focus on the cognitive component. To realise the purpose and objectives of the paper, a set of tests (the Test of the Life-Sense Orientations; the Purpose-in-Life Test (PIL); and a questionnaire of early childhood decisions, etc. were used as diagnostic tools to find out the correlation between components of professional success. Statistical correlation was analysed with the use of Pearson’s correlation coefficient. Results. The results of the correlation analysis between the indicators of personal readiness for change and the scenarios show a reversed two-way correlation between the indicators of the Confidence scale and the attributes “Don’t be, don’t be alive”, “Don’t be yourself”, “Be excellent”; between the metrics of the “Passion” scale and the “Don’t grow up”, “Don’t be yourself”. Conclusion. It was found that meaningful orientations of the future primary school teachers and scenario settings like “Do Not Get Close, Don’t Love, Don’t Feel, Be Perfect, Try, function as psychological barriers to achieving professional success.